CONSPECTUS OF TRICHOSANTHES (CUCURBITACEAE) IN MALESIA - RUGAYAH RUGAYAH; W. J. J. O DE WILDE (REINWARDTIA, 1999)
Trichosanthes (Cucurbitaceae) in Malesia comprises 5 sections with 39 species, here alphabetically arranged. Key to the sections, keys the species within the sections and eight regional keys are presented Twenty-five taxa are newly proposed: 1 section, 14 species, 1 sub species, 2 varieties and 7 forms.